The Relationship Between Family Sanitation and Stunting (A Case Study in the Ampenan District, Mataram City) - Pratama, Lalu Galih Putra; Suripto, Suripto; Ernawati, Ernawati (Jurnal Biologi Tropis, 2026)
A densely populated urban area with slum areas, such as Ampenan District, Mataram City, has a risk of worsening sanitation and nutritional status of toddlers. This study aimed to determine the effect of family sanitation on the incidence of stunting in Ampenan District. A total of 99 toddlers and their families were taken as samples through purposive sampling. Stunting data was collected through the PPGBM electronic document review technique from community health centers in Ampenan District. Sanitation data was collected through interviews with the families of the toddlers. The test of the relationship between sanitation and stunting was approached using regression analysis. The prevalence of stunting in Ampenan District is relatively low (6.03%), with the highest vulnerability in toddlers aged 25–36 months. Family sanitation (X) had a significant positive effect on the nutritional status (Z-score) of toddlers (Y), with the model Y = -7.4532 +0.0744 X. The implication is, to target stunting prevention (Z score >-2) in Ampenan, the sanitation score must be >73.3.